2022
DOI: 10.1038/s41598-022-21552-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of super-class cannabis terpenes beta-caryophyllene and alpha-pinene on zebrafish behavioural biomarkers

Abstract: Terpenes possess a wide range of medicinal properties and are potential therapeutics for a variety of pathological conditions. This study investigated the acute effects of two cannabis terpenes, β-caryophyllene and α-pinene, on zebrafish locomotion, anxiety-like, and boldness behaviour using the open field exploration and novel object approach tests. β-caryophyllene was administered in 0.02%, 0.2%, 2.0%, and 4% doses. α-pinene was administered in 0.01%, 0.02%, and 0.1% doses. As α-pinene is a racemic compound,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Our terpenoid analysis demonstrated that the six cultivars have very different terpenoid compositions, which could explain the varied aromas and flavors associated with each cultivar (Table ). The values found with these cannabis terpenoids agree with those published elsewhere. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our terpenoid analysis demonstrated that the six cultivars have very different terpenoid compositions, which could explain the varied aromas and flavors associated with each cultivar (Table ). The values found with these cannabis terpenoids agree with those published elsewhere. , …”
Section: Resultssupporting
confidence: 91%
“…The values found with these cannabis terpenoids agree with those published elsewhere. 55,56 For the untargeted GC−MS terpenoid assay, the analytes were putatively identified at a confidence level of two. The identification criteria were based on a combination of the RIs and matching the experimental electron impact (EI)−MS fragmentation patterns of the corresponding compounds with the EI−MS spectra in the NIST20 GC−MS library.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When used in zebrafish behavioral assays, including an open field-exploration test and a novel object approach test, BCP revealed no effect on anxiety and swimming velocity, while decreasing immobility ( Table 1 ). BCP had only a sedative effect at the highest dose tested [ 109 ]. Taken together, the results of this study indicated a potential dose-dependent downward trend in anxiety levels, which may require an increased dosage.…”
Section: Bcp As a Functional Cb2r Agonist To Target Neuropsychiatric ...mentioning
confidence: 99%
“… Mice DSS-induced anxiety ↓ Anxiety [ 108 ] BCP (chronic; 0.02, 0.2, 2, 4%; p.o. in dosing beaker) Zebrafish Acute stress ↓ Immobility at the highest dose used (i.e., 4%) No effect on anxiety [ 109 ] BCP (chronic; 10 mg/kg; p.o.) BALB/c mice STZ-induced diabetes ↓ Depressive-like behavior ↓ IL-1β ↓ TNFα ↓ IL-6 [ 110 ] …”
Section: Bcp As a Functional Cb2r Agonist To Target Neuropsychiatric ...mentioning
confidence: 99%
“…Particularly in C. sativa, Chacon and coworkers found that terpenes may vary between 0.001 and 14.8 mg/g of the dry weight of the plant [39] and are in general rich in mono-and sesquiterpenes [34]. Monoterpenes, structurally characterized by a skeleton with two molecules of isoprene, are more volatile and contribute to the flavor and aroma of the plant, while sesquiterpenes (structure containing three molecules of isoprene) are more stable and contribute to the therapeutical benefits of the plant [40]. The monoterpene β-myrcene and the sesquiterpenes β-caryophyllene and α-humulene have been identified in most cannabis species, including C. sativa.…”
Section: Cannabinoidsmentioning
confidence: 99%